Medication Errors and Reducing Interventions: A Mixed Study in a Teaching Hospital - Serajaddin Gray; Mohammad Effatpanah; Sara Salehi; Siamand Anvari Savojbalaghi; Leila Momeni; Roghayeh Abedi Gilavandani; Alireza Abbasi Chaleshtari (Research Center for Rational Use of Drugs (RCRUD), 2021)
Background: Given the special importance of preventing from medication, the present study aimed to investigate the determining Causes of Medication Errors (CMEs) and their Priorities for reducing interventions in a hospital.Methods: The present mixed, sequential and cross-sectional study was conducted in a teaching hospital (2016). For data collection, Fishbone Diagrams, interviews, note taking and checklists were used, and qualitative data were analyzed though the thematic approach. Moreover, the Maxqda Software v.14.0, Excel, Edraw Max v.9.0 were employed for data analysis and reporting.Results: Seventy-five CMEs were classified under two main themes (human and non-human) and four sub-themes (personal, network, organizational, and meta-organizational). Weakness of professionalism and low experience as the personal causes; Actions of pharmacy colleagues, physicians and other nurses as the network causes; Management of nurses and unit specialty as the organizational causes and the quality of academic education, drug features and macro policies of medication as meta-organizational causes were classified. Six causes were given priority for reducing interventions.Conclusion: In the short term, human factors should be considered with the aim of reducing medication errors. It is also recommended that teaching how to deal with nurses' stress and psychological pressure (especially beginner nurse), resulting from critically ill patients and high workload, be paid special attention. Besides, it is suggested that professionalism be given priority to reduce personal neglects and to create safe environments for reporting personal neglects. In addition, more emphasis should be placed on the right route in the process of medication administration.